Conocimiento de los representantes de personas con capacidades especiales sobre salud bucal - Ivette Yadira, Gómez Llerena (2022)
ABSTRACT: The objective of this research work was to analyze the level of knowledge about oral health that tutors of people with special needs have. The type of research was descriptive cross-sectional and non-experimental. The population were 150 people who work with people with special needs. The current research work was carried out in three different places. The first one was the GAD-Mocha; it showed that tutors who work with people with special needs have a high level of knowledge about oral health. It was between 50% and 58%. The second place was San José Foundation in Huambalo-Pelileo; it was determined that tutors from that foundation have a low level of knowledge about oral health; the results showed a 50%.Finally, the tutors of the GAD-Patate demonstrated a medium level of knowledge about oral health with the 41.66%. As a conclusion, some people have an idea about the correct oral hygiene for themselves and their pupils care.